MULTIMODAL APPROACH AS AN EFFECTIVE SOLUTION FOR DEVELOPING PROFESSIONAL COMPETENCE OF FUTURE ENGLISH TEACHERS - Alimova Dildora Komiljon qizi, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
The rapid development of digital technologies and the transformation of educational systems require innovative pedagogical approaches in teacher education. One of the most promising approaches is the multimodal approach, which integrates different modes of communication in the learning process. This article examines the role of multimodal learning in developing the professional competence of future English language teachers. The study is based on the analysis of modern pedagogical literature and international educational practices. The findings indicate that the multimodal approach significantly enhances communicative, methodological, and digital competencies of pre-service teachers. The study concludes that multimodal teaching strategies contribute to more effective teacher training in modern educational contexts.